Does body position before and during blood sampling influence the Athlete Biological Passport variables?. (10th December 2019) - Astolfi, Tiffany; Schumacher, Yorck Olaf; Crettaz von Roten, Fabienne; Saugy, Martial; Faiss, Raphael
Abstract: Introduction: The Athlete's Biological Passport (ABP) is a tool for the indirect detection of blood doping. Guidelines from the World Anti‐Doping Agency (WADA) require a 2 hours delay after any physical exercise, and to be seated for 10 minutes before collecting an ABP sample. This study investigated posture‐related hematological variations with changes in body position during blood sampling. Methods: Ten successive venous blood samples from 38 subjects were collected in three situations: immediately after 10‐minutes of normalized activity (B1), after 10‐minutes seated (B2, typical reference sample in an anti‐doping context), after a 50 m walk (B3), after 5 and 10‐minutes in a seated position again (B4 and B5), and finally after 5‐30 minutes supine (B6‐B10). Hemoglobin concentration [Hb] and hematocrit (Hct) were determined by flow cytometry to assess putative posture‐related variations. Results: Reticulocytes percentage was unchanged in all conditions, [Hb] and Hct were stable after at least 10‐minutes in a seated position. Due to shifts in plasma volume, [Hb] and Hct increased slightly but significantly higher after changing posture for a short walk (+0.1 gr/dL [ P = .008] and +0.4% [ P = .01] respectively), but readjusted to previous levels after only 5 minutes. Supine position (>10 minutes) induced decreases of [Hb] (−0.2 g/dL in average, P < .01) and Hct (−1.1%, in average, P < .01). Conclusion: The observed variations in [Hb] and Hct may have minor clinical significance, while they underline the need to follow strict guidelines for posture before and during blood sampling in an anti‐doping context.